Comparisons of Dose-Volume Histograms for Proton-Beam versus 3-D Conformal X-Ray Therapy in Patients with Stage I Non-Small Cell Lung Cancer - Wang, Changlu; Nakayama, Hidetsugu; Sugahara, Shinji; Sakae, Takeji; Tokuuye, Koichi (Strahlentherapie und Onkologie, 2009)
Purpose: Dose-volume histograms (DVHs) were reviewed to determine if there is an advantage of the two modalities when treating patients with non-small cell lung cancer (NSCLC). Patients and Methods: 24 stage I NSCLC patients who underwent proton-beam therapy (PBT) from June 2003 to May 2007 were included in this study. Based on the same clinical target volumes (CTVs), treatment planning was made to cover CTV within 90% isodose lines. Each patient was evaluated by two sets of DVHs, one for PBT and the other for three-dimensional conformal X-ray therapy (3D-CRT). Results: For all patients, the 95% isodose line covered 86.4% of the CTV for PBT, and 43.2% for 3D-CRT. PBT was associated with significantly lower mean doses to the ipsilateral lung, total lung, heart, esophagus, and spinal cord than 3D-CRT. PBT offered reduced radiation doses to the lung when evaluated in terms of percentage lung volumes receiving ≥ 5 Gy (V 5 ), ≥ 10 Gy (V 10 ), and ≥ 20 Gy (V 20 ) when compared to 3D-CRT. Conclusion: PBT is advantageous over 3D-CRT in reducing doses to the lung, heart, esophagus, and spinal cord in treating stage I NSCLC.